(untitled) (Teaching and Learning Inquiry, 2020)
The Scholarship of Teaching and Learning (SoTL) encompasses research on postsecondary teaching and learning across all disciplines. Why do scholars engage in the study of teaching and learning? What supports and challenges do they encounter? What is the impact of SoTL? Using a micro-meso-macro-mega (4M) framework, I explore these questions in interviews with seven SoTL scholars from various disciplines in one institution. Primarily, this article provides a case study illustration of the use of the micro-meso-macro-mega framework to explore SoTL. In addition to exploring participants’ reflections vis-à-vis the four levels, I reflect on possible connections to motivation theory as a lens for themes arising from the participants’ accounts of supports and barriers and the impact of their SoTL work.